RNA methylation in neurodevelopment and related diseases - Xia Wenjuan; Liu Yue; Lu Jiafeng; Cheung Hoi-Hung; Meng Qingxia; Huang Boxian (Acta Biochimica et Biophysica Sinica)
Biological development and genetic information transfer are governed by genetic, epigenetic, transcriptional, and posttranscriptional mechanisms. RNA methylation, the attachment of methyl (–CH3) groups to RNA molecules, is a posttranscriptional modification that has gained increasing attention in recent years because of its role in RNA epitranscriptomics. RNA modifications (RMs) influence various aspects of RNA metabolism and are involved in the regulation of diverse biological processes and diseases. Neural cell types emerge at specific stages of brain development, and recent studies have revealed that neurodevelopment, aging, and disease are tightly linked to transcriptome dysregulation. In this review, we discuss the roles of N6-methyladenine (m6A) and 5-methylcytidine (m5C) RNA modifications in neurodevelopment, physiological functions, and related diseases.